THU0080 Serum irisin and myostatin levels in patients with rheumatoid arthritis. (12th June 2018) - Silva, J.M.D.S.; Santo, R. C. D. E.; Freitas, E.C.; Braz, N.F.T.; Vieira, É.L.M.; Guimarães, M. F. B. R.; Silva, A. C. S. E.; Kakehasi, A.M.; Xavier, R.M.
Abstract : Background: Rheumatoid arthritis (RA) patients have loss of muscle mass. The balance between muscle protein synthesis and degradation is regulated by cytokines and growth factors, named myokines, such as irisin and myostatin. Myokines are mainly expressed by skeletal muscle and exert systemic effects promoting crosstalk among different tissues. Irisin increases cortical bone mass and its low levels are related to muscle atrophy and obesity[, 1, 2 while myostatin is a negative regulator of muscle growth and regeneration and has a direct role in osteoclastogenesis of inflammatory bone destruction[. 3, 4 Objectives: To evaluate serum levels of irisin and myostatin and body composition of RA patients and controls. Methods: 122 female patients with RA, mean age 53 years, mean disease activity score (DAS28) 4.09, mean disease duration 11.2 years and mean body mass index 27.33 kg/m 2 were included. 69 age and sex-matched healthy subjects were enrolled as control group. Irisin (Phoenix Pharmaceuticals) and myostatin (R and D Systems) serum levels were evaluated by ELISA. Fat mass index (FMI;Kg/m 2 ) and appendicular lean mass index (ALMI;Kg/m 2 ) were assessed by total body dual-energy x-ray absorptiometry. Student's t test and Spearman correlation were performed. Significance was set at p<0.05. Results: RA patients had decreased serum levels of irisin (25, 61±8, 25 vs 30, 36±10, 95 ng/ml; p<0.05) and myostatin (3011, 28±1271, 11 vs 4049, 08±1610, 01 pg/ml; p<0.05), decreased ALMI (6, 09±0, 88 vs 6, 50±1, 10; p<0.05) and increased FMI (11, 26±3, 30 vs 9, 44±2, 65; p<0.05), compared to controls. No correlations were observed among irisin and myostatin levels and ALMI and FMI. Of the 122 RA patients, 40 were analysed for the use of biologic medication. Serum levels of irisin and myostatin were different between RA patients treated and non-treated with biologics (table 1). Conclusions: RA patients presented loss of lean mass and gain of fat mass, as well as lower irisin and myostatin serum levels, in comparison with controls. Additionally, the use of biologic medication by patients impacted on myokines serum levels. Further analyses are needed for a better comprehension of irisin and myostatin roles in RA, and to verify their correlation to other RA features. References: [1] Colaianni G, et al. Proc Natl Acad Sci2015;112(39):12157–62. [2] Chang J, et al. Geriatr Gerontol Int. 2017;17(11):2266–2273. [3] Huang Z, et al. Cell Signal2011;23(9):1441–6. [4] Dankbar B, et al. Nat Med2015;21(9):1085–90. Disclosure of Interest: None declared